(untitled) (Academicia Globe: Inderscience Research, 2021)
Greeting- is expressive speech act, and refers to socio-pragmatics. The typical L2 classroom usually provides too little examples of this extremely important phase of communication. Just knowing the words of a language is only one part of speaking it, it is equally important to know how and where to use and interpret them. Greeting is a speech act that child is taught explicitly in his native language. The importance and communicative function of greeting is often understood as subordinate. It means that greetings are used to support the ultimate goal of communication. Language classrooms often neglect teaching greeting appropriately, there is no enough attention to the role of greeting, but greetings play a great role in a different cultures and communities and may affect the ultimate goal of communication. The form of the greetings depends on the context, and context here considers the relationship between the people. Success in delivering greetings appropriately can be taught and assessed in a classroom context, but the general aim is to teach students how to behave themselves in unexpected situations in the real world.